2017
DOI: 10.1371/journal.pone.0176652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mild hypothermia preconditioning against low temperature (4°C) induced rat liver cell injury in vitro

Abstract: Bioartificial liver holds special position in the field of regenerative medicine, and cold environment at 4℃ is widely used for the short storage of both organ and liver cell for later application. However, the disadvantages of such cold storage could influence cell viability and lead to cell apoptosis in different degrees. In this study, we mainly explore the pre-protective effect of mild hypothermia against low temperature (4℃)-induced rat liver cell injury in vitro. Our results indicated that the preconditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
(39 reference statements)
2
7
0
Order By: Relevance
“…Apoptosis was observed in the liver tissue under thermal stress, which showed that both cold and heat stress can increase the rate of apoptosis in hepatocytes and disrupt the normal morphology of liver cells. This finding is consistent with results obtained in pufferfish (Cheng et al, 2015(Cheng et al, , 2017 and rat (Ates et al, 2006;Qin et al, 2017). Accordingly, acute thermal stress can induce the apoptosis of hepatocytes and cause the dysfunction of liver metabolism.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Apoptosis was observed in the liver tissue under thermal stress, which showed that both cold and heat stress can increase the rate of apoptosis in hepatocytes and disrupt the normal morphology of liver cells. This finding is consistent with results obtained in pufferfish (Cheng et al, 2015(Cheng et al, , 2017 and rat (Ates et al, 2006;Qin et al, 2017). Accordingly, acute thermal stress can induce the apoptosis of hepatocytes and cause the dysfunction of liver metabolism.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we investigated the effects of both cold and heat stress on liver histology, apoptotic index, antioxidant activity indices and stressresponse gene expression in the giant spiny frog Q. spinosa. Histological and ultrastructural alterations were observed in the liver under thermal stress, and the hepatic cells were partially degenerated, necrotic and accompanied with increased apoptosis, which is consistent with results in the Chinese fire-belly newt Cynops orientalis (Wang et al, 2012) and rat (Ates et al, 2006;Qin et al, 2017). In this study, erythrocyte abnormalities, including hemorrhage and congestion, were present in liver tissues under cold and heat stress, which could be attributed to the destruction of hepatic erythrocytes and accumulation of newly produced erythrocytes in the liver (Maekawa et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…Long-standing pathologic hypertrophy will contribute to heart disorder and eventually increases the mortality and morbidity of chickens [ 4 ]. Of note, it has been well documented that exposure to low temperature induced the elevation of oxidative metabolism and heat production, accompanied by elevated reactive oxygen species (ROS) production and the oxidative stress in heart and liver [ 5 ]. In turn, oxidative damage further aggravates heart and liver dysfunction, which weakens the chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Last, but not least, PI3K/Akt/GSK-3b is known to be a prosurvival pathway, as it inhibits the opening of the mitochondrial transition pore, which leads to cell apoptosis. 44 Therefore, the effect of PI3K/Akt/GSK-3b in VEC injury induced by acute lower limb IR in rats should be further verified.…”
Section: Discussionmentioning
confidence: 97%